Nilai-Nilai Spritual dalam Tradisi Tahlil Pasca Hari Raya ‘Idul Fitri di Dusun Lanpelan, Sana Laok, Waru, Pamekasan: (Studi Analisis Perspektif ayat-ayat Sosial) - Bakir, Moh.; Wijaya, Subur (STAI Al-Mujtama Pamekasan, 2024)
The results of this research prove that the tradition of post-Eid al-Fitr tahlilan activities for three days with each resident taking turns has been going on for a long time. This tradition basically becomes a medium for sharing, praying for each other, strengthening friendship, and in order to preserve spiritual values ​​in the month of Ramadan. More than that, this tradition becomes a medium for preaching to the community. Apart from that, the tradition of tahlilan activities and group prayer after carrying out the Eid al-Fitr prayer service is a way for the residents of Lanpelan Hamlet, Sana Laok Pamekasan to preserve spiritual values. The values ​​contained in this tradition, from a social perspective, include the spirit of giving alms, working together, instilling an attitude of solidarity and maintaining harmony. This research uses a qualitative approach, taking the location of Lanpelan Hamlet, Sana Laok Waru, Pamekasan. The analysis technique used in this research is interactive analysis, such as data reduction, data display, and conclusions. Data collection methods through observation, interviews and documentation techniques. Keywords: Values, Spiritual, Tahlilan, Eid al-Fitr, Society